If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-4)2=-64
We move all terms to the left:
(x-4)2-(-64)=0
We add all the numbers together, and all the variables
(x-4)2+64=0
We multiply parentheses
2x-8+64=0
We add all the numbers together, and all the variables
2x+56=0
We move all terms containing x to the left, all other terms to the right
2x=-56
x=-56/2
x=-28
| (x-4}2=-64 | | 3(4x-10)=8x+5 | | 2(q-92)=14 | | 7v+7=28 | | 3(4x-10)=8x+-5 | | -14r=8-15r | | 18w+4=20w | | -4y+18=4y+20 | | 3+3n=-2n | | 8b+3=10b-15 | | -2x+40=10 | | 3(4x-10)=8x+ | | 5x+4=15x-2 | | 5b=4b+10 | | -20+6+14c=12c+20 | | 12y+18=18y-6 | | 4x^2=50+2x^2 | | 11u-14=12u-18 | | 4x^2=50+2x^ | | 2b-12=b+20 | | 10q=9q-17 | | 6(2w-8)+3=15 | | 3n-4=1n-3n+11 | | 7/2x+1=4 | | 2(12+1x)=2x+24 | | 3n-4=1n-3n=11 | | 2b=b+b | | 10d+9=3d-9+9d | | -27=-(y-47) | | -3-p=9+2p | | 4(z+16)=92 | | 5n+3=2n+ |